Minors migrants repatriated unaccompanied in Reynosa, Tamaulipas: A descriptive analysis of the migration flow - Vargas-Orozco, Cynthia Marisol (Universidad Autónoma de Tamaulipas, 2012)
The migration of children and young people has traditionally been understood as part of a strategy to looking for family togetherness. The phenomenon of children and young people who travel alone across international borders is becoming more frequent. The migration of unaccompanied minors is but a manifestation of the changes that migration processes are experienced in recent years. Faced with this problem, the study description makes a reflection on the causes and factors that motivate migration of unaccompanied minors, who were repatriated across the border from Reynosa, Tamaulipas- McAllen, Texas (USA), during the study period from January 2008 to December 2009. Just as the dominant genre of migration flows, the age range and nationality.